Pelatihan Bahasa Arab Fungsional Kepada Dosen Ilmu Umum Di Lingkungan UIN Imam Bonjol - Mahyudin Ritonga; Asrina Asrina (Jurnal Pengabdian UntukMu NegeRI, 2022)
Lecturers in STAIN / IAIN / UIN and at PTKIS are not always from Islamic-based institutions, because the departments available at PTKI institutions are also very diverse. Meanwhile, the people around the lecturer's residence do not understand the background of lecturers who teach at UIN, the community only knows that they are UIN lecturers and they are of the view that every lecturer who teaches at UIN is an SDM who has religious and Arabic skills. Therefore, it is necessary to hold activities that can help general lecturer knowledge of the Arabic language. This activity is carried out in the form of training with the delivery of materials by speakers and demonstrations of trainees. Results of the activities it can be explained that lecturers with general education backgrounds who initially have no knowledge of Arabic, but after training activities they are able to ask and answer with Arabic for usual conversations in everyday life.